Large nabothian cyst with chronic pelvic pain: case report and literature review - H.K. Kim; S.H. Park; C.J. Kim; J.Y. Kwon; J. Namkung (Clinical and Experimental Obstetrics & Gynecology, 2020)
The authors report a rare case of a large nabothian cyst with chronic pelvic pain in 48-year-old woman. The patient suffered from chronic pelvic pain radiating to the right leg, especially during ambulation. The large cystic mass was found in the cervix. A cystectomy was performed through the vagina. Nabothian cyst was pathologically confirmed and the patient’s pelvic pain improved postoperatively.